Determination of flexible availabilty for management and operation of electric vehicle charging stations - Medeiros, Aerton P.; Farias, Hericles E. O.; Rangel, Camilo A. S.; Canha, Luciane N.; Garcia, Vinicius J.; Santos, Rodrigo B. Dos (IEEE Power & Energy Society General Meeting, 2023)
The present work aims to address the growing interest in the subject of flexibility. For this, the study estimates flexibility potential available in an electric vehicle charging station (EVCS) to service public recharges, which serves scheduled and unscheduled recharges. The considered EVCS operates with the existence of photovoltaic generation and battery energy storage system (BESS). In the case study, the flexible avaibility for each one of the 24 hours in the EVCS operation is presented, estimated according to the methodology presented, considering the management of the EVCS operation performed in real time with 1 minute discretization.